A wide‐targeted urinary and serum metabolomics strategy reveals the effective substance of the Wu‐tou decoction. Issue 4 (11th December 2019) - Cheng, Xiaoxu; Xu, Tengfei; Pi, Zifeng; Liu, Shu; Song, Fengrui; Liu, Zhiqiang
Abstract: As an important Chinese medicine decoction, Wu‐tou decoction has been used to treat rheumatic arthritis for more than a thousand years. We previously reported that the Wu‐tou decoction could change the urinary and serum metabolites in adjuvant‐induced arthritis rats significantly. The purpose of this research was to confirm the potential biomarkers obtained by previous non‐targeted metabolomics study through quantitative analysis by liqui chromatography with tandem mass spectrometry, in the meantime, to further study the effective material basis of Wu‐tou decoction. Firstly, the important compounds in the tryptophan metabolism pathway, the arginine and proline metabolism pathway, the amino acid metabolism pathway, the tricarboxylic acid cycle, the vitamin B6 metabolism pathway, and the phenylalanine metabolism pathway, which were identified as potential biomarkers in previous study, were selected for quantitative analysis. Then the linearity, limit of detection, limit of quantification, selectivity, accuracy, precision, stability, recovery, and matrix effect of the quantitative method were examined. Finally, ten and eighteen metabolites were quantitatively analyzed in the serum and urine, respectively. The results showed that seven out of ten serum potential biomarkers and ten out of eighteen urine potential biomarkers were confirmed as real biomarkers. This research provides a powerful reference for the study on effective material basis of Wu‐tou decoction.